The impact of photofunctionalized gold nanoparticles on osseointegration. Issue 7 (July 2018) - Elkhidir, Yassir; Lai, Renfa; Feng, Zhiqiang
Abstract: Objectives: The aims of this study were to create a new surface topography using simulated body fluids (SBF) and Gold Nanoparticles (GNPs) and then to assess the influence of UV Photofunctionalization (PhF) on the osteogenic capacity of these surfaces. Materials and methods: Titanium plates were divided into six groups All were acid etched with 67% Sulfuric acid, 4 were immersed in SBF and 2 of these were treated with 10 nm GNPs. Half of the TiO2 plates were photofunctionalized to be compared with the non-PhF ones. Rat's bone marrow stem cells were seeded into the plates and then CCK8 assay, cell viability assay, immunofluorescence, and Scanning electron microscopy (SEM) were done after 24 hours. Gene expression analysis was done using real time quantitative PCR (qPCR) one week later to check for the mRNA expression of Collagen-1, Osteopontin and Osteocalcin. Alkaline phosphatase (ALP) activity was assessed after 2 weeks of cell seeding. Results: Our new topography has shown remarkable osteogenic potential. The new surface was the most biocompatible, and the 10 nm GNPs did not show any cytotoxicity. There was a significant increase in bioactivity, enhanced gene expressions and ALP activity. Conclusions: GNPs enhances osteogenic differentiation of stem cells and Photofunctionalizing GNPs highly increases this. We have further created a novel highly efficient topography which highly enhances the speed and extent of osseointegration. This may have great potential for improving treatment outcomes for implant, maxillofacial as well as orthopedic patients.